2019
DOI: 10.4064/cm7349-6-2018
|View full text |Cite
|
Sign up to set email alerts
|

Cardinal Invariants for the $G_\delta $ topology

Abstract: We prove upper bounds for the spread, the Lindelöf number and the weak Lindelöf number of the G δ topology on a topological space and apply a few of our bounds to give a short proof to a recent result of Juhász and van Mill regarding the cardinality of a σ-countably tight homogeneous compactum.2000 Mathematics Subject Classification. Primary: 54A25, Secondary: 54D20, 54G20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Third, a result of Bella and Spadaro from [6] follows as a corollary to the Main Theorem and can be strengthened to the power homogeneous setting. In that paper Theorem 1.1 was extended using the G δ -modification X δ by showing that if X is a homogeneous compactum which is the union of countably my dense countably tight subspaces, then L(X δ ) ≤ c. Using the Main Theorem, we show in Theorem 4.7 that this result holds even if the homogeneity property is replaced with the weaker power homogeneity property.…”
Section: Introductionmentioning
confidence: 93%
“…Third, a result of Bella and Spadaro from [6] follows as a corollary to the Main Theorem and can be strengthened to the power homogeneous setting. In that paper Theorem 1.1 was extended using the G δ -modification X δ by showing that if X is a homogeneous compactum which is the union of countably my dense countably tight subspaces, then L(X δ ) ≤ c. Using the Main Theorem, we show in Theorem 4.7 that this result holds even if the homogeneity property is replaced with the weaker power homogeneity property.…”
Section: Introductionmentioning
confidence: 93%
“…Given a topological space X we can consider a finer topology on X by declaring countable intersections of open subsets (or zero-sets) of X to be a base (see [4,9]). The new space is called the G δ topology of X and is denoted with X ℵ 0 (X δ in paper [6]). Note that the topology X ℵ 0 coincides with the weak topology generated by B α (X) for each α > 0 ( [17]).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes a neat ZFC bound is avaliable. For example, Juhász [9] proved that c(X δ ) ≤ 2 c(X) for every compact Hausdorff space X, where c(X) denotes the cellularity of X, Bella and the author [4] proved that s(X δ ) ≤ 2 s(X) for every Hausdorff space X, where s(X) is the spread of X and Carlson, Porter and Ridderbos [6] showed that L(X δ ) ≤ 2 F (X)•L(X) for every Hausdorff space X (the F (X) in the exponent cannot be removed in the last result as there are even compact spaces whose weak Lindelöf number is larger than the continuum, see [15]). In other cases the existence of a bound may strongly depend on your set theory.…”
Section: Introductionmentioning
confidence: 99%